ANALISIS KOMPARATIF USAHATANI PADI SAWAH YANG MENGGUNAKAN VARIETAS CILIWUNG DAN CIGEULISDI DESA TATAKALAI KECAMATAN TINANGKUNG UTARA KABUPATEN BANGGAI KEPULAUAN - Ismail Zen; Made Antara; Rustam Abd. Rauf (Universitas Tadulako, 2017)
The research aims were 1) to determine the production and income of wetland rice farming system of Ciliwung and Cigeulis varieties, and 2) to determine the disparities of the production and income of the wetland rice farming system of Ciliwung and Cigeulis varieties in Tatakalai village of North Tinangkung sub district. Population of the research was 325 farmers who were cultivating wetland rice and members of farmer groups. The number of samples was 50 people. Data collected was analyzed using income analysis and production and income comparison analysis. The incomes of the farmers were IDR 5,959,921.79/ha for those who planted Ciliwung variety and IDR 9,255,957.70/ha for those who planted Cigeulis variety. There was no significant different in the rice productions between the two varieties but the average incomes of both varieties farming system was significant.Keywords : Income, Production and Wetland Rice Farming System.